(untitled) (Journal Of Educational and Psychological Researches, 2015)
Psychological Counseling Services occupies a high position in the developed countries and that for its psychologist services for different sectors of the community members, and has been popularized until recently the wrong concept of the effect, that the psychological service is provided only to the owners of behavior is normal only, Vantage him neglect to provide psychological services a large segment of the community members who are in dire need of these services. The counseling service is part of a global social movement seeking to emphasize the quality of life of the human and the emphasis on the value and dignity and the need to live a quiet life of happiness and away from sources of misery and confusion. Although the concept of quality is mainly given to the physical and technological side, it can use the same concept to denote a human, function and honorable building and the fact that human quality is good hire mental and creative potential and enrich the conscience of the orphan his emotions and feelings and human values . And the result is the quality of life and the quality of the community and this is through the family, the school and the university environment and the work environment . in light of this highlights the importance of research to clarify the role of psychology and counseling to achieve the quality of life and the development of viable recommendations for implementation with clarifying the role of the university and the community to achieve. We try in the current context to clarify the role of psychological counseling in improving the quality of human life that witnessed by the contemporary society and to achieve this goal should be to focus on psychological counseling and the need for it in contemporary society . Secondly, the research objectives The current research aims to identify: 1. The role of psychological counseling to achieve the quality of life. 2. The role of psychological counseling to achieve the quality of life in descending order by weight percentile. Third: the limits of search Is determined by current research professors University of Baghdad and the Iraqi university for the academic year 2014-2015. Fourth, determine the terms Chapter II ....... included theoretical framework to guide the psychological and quality of life. Chapter III .... includes statistical procedures. Chapter IV ... research and recommendations and proposals results.